Analysis of Village Government Efforts to Improve Public Services in Tanah Mea Village, West Kutai Regency - Einsbie Grata Myn; Muhammad Kasim; Ela Yusrianti (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to analyze the efforts of the Tanah Mea village government, West Kutai Regency in improving the quality of public services. The research method uses a case study approach to explore in order to obtain an interpretation of the